ChemInform Abstract: Copper‐Catalyzed Borylative Cross‐Coupling of Allenes and Imines: Selective Three‐Component Assembly of Branched Homoallyl Amines. Issue 21 (6th May 2016) - Rae, James; Yeung, Kay; McDouall, Joseph J. W.; Procter, David J.
Abstract: A series of branched α, β‐substituted‐γ‐boryl homoallylic amines (IV) is prepared by three‐component reaction of imines (I) with allenes (II) and bis(pinacolato)diboron (III) in the presence of a copper catalyst.